2018
DOI: 10.3762/bjnano.9.20
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-dependent wound sealing in succulent leaves of Delosperma cooperi – An adaptation to seasonal drought stress

Abstract: During evolution, plants evolved various reactions to wounding. Fast wound sealing and subsequent healing represent a selective advantage of particular importance for plants growing in arid habitats. An effective self-sealing function by internal deformation has been found in the succulent leaves of Delosperma cooperi. After a transversal incision, the entire leaf bends until the wound is closed. Our results indicate that the underlying sealing principle is a combination of hydraulic shrinking and swelling as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…), and impedes further fissure propagation. The driving forces involved are mostly physical reactions such as the swelling of cells, the melting of waxes, and the deformation of wound tissues or entire organs [ 6 ]. Subsequently, during the long-lasting self-healing phase, the damage is structurally repaired by a process characterized by cell division and tissue regeneration, both of which restore (at least partly) mechanical properties and functions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…), and impedes further fissure propagation. The driving forces involved are mostly physical reactions such as the swelling of cells, the melting of waxes, and the deformation of wound tissues or entire organs [ 6 ]. Subsequently, during the long-lasting self-healing phase, the damage is structurally repaired by a process characterized by cell division and tissue regeneration, both of which restore (at least partly) mechanical properties and functions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…), a rapid self-sealing phase initiates self-repair and restores the functional integrity of the leaf preventing any further loss of stored water from the system. Subsequently, a comparatively slow self-healing phase restores structural integrity and, hence, in part the mechanical properties of the leaf [ 8 , 15 , 16 ]. The quick initial self-sealing phase is of particular interest, as it involves a deformation of the entire leaf rapidly bringing the wound edges into contact and preventing further water loss.…”
Section: Introductionmentioning
confidence: 99%
“…The deformation of D. cooperi leaves during self-sealing differs dependent on the type of wound applied to the leaf. If a longitudinal or transversal cut is applied unilaterally, i.e., only on one side of the leaf, the leaf will bend towards the side of the incision leading to the sealing of the wound [ 15 , 16 ]. If an injury is applied around the circumference of the leaf, the entire leaf will perform a contraction along the leaf axis [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies of artificially injured plant organs have revealed various wound reactions that can be subdivided into a fast selfsealing phase followed by a markedly slower self-healing phase, both being included under the umbrella term of self-repair (Harrington et al 2015). Mechanical damage is immediately followed mainly by physical reactions causing rapid self-sealing that include: (i) tissue deformation in the wounded region (Anandan et al 2018;Speck et al 2018), and (ii) discharge of mucilage (Zimmermann and Granata 2002;Anandan et al 2018). During the subsequent self-healing phase, chemical reactions and more complex biological responses dominate such as: (i) coagulation of latex (Bauer and Speck 2012), (ii) local lignification of tissues (Paul-Victor et al 2017), (iii) formation of a (ligno-suberized) boundary layer (Rittinger et al 1987;Evert 2006), and (iv) development of a wound periderm (Evert 2006).…”
Section: Introductionmentioning
confidence: 99%